013 Modulating mitochondrial dynamics as a novel cardioprotective strategy. (22nd September 2015) - Ong, S B; Arjun, S; Lim, S Y; Davidson, S M; Yellon, D M; Hausenloy, D J
Abstract : Introduction: Mitochondria change their shape by undergoing either fusion or fission producing elongated interconnected or fragmented discrete networks, respectively. Whether alterations in mitochondrial morphology impact on the heart's susceptibility to ischaemia-reperfusion injury is unknown. We hypothesised that inducing mitochondrial fusion protects the heart against ischaemia-reperfusion injury. Methods and Results: In response to ischaemia, mitochondria in HL-1 cells (a cardiac-derived cell line) were shown to undergo fragmentation, a process which could be prevented by a dominant negative construct of Dynamin-related protein 1 (Drp1, a known mitochondrial fission protein). Inducing mitochondrial fusion in HL-1 cells by over-expressing either mitofusin 1 or 2 (known mitochondrial fusion proteins) or Drp1K38A (a dominant negative mutant form of Drp1): increased the proportion of cells containing elongated mitochondria (65±4%, 69±5%, 63±6%, respectively, vs 46±6% in control:N=80 cells/group; p<0.05); decreased mitochondrial permeability transition pore sensitivity (by 2.4±0.5, 2.3±0.7, 2.4±0.3-fold, respectively; N=80 cells/group: p<0.05); and reduced cell death following simulated ischaemia-reperfusion injury (11.6±3.9%, 16.2±3.9%, 12.1±2.9%, respectively, vs 41.8±4.1% in control:N=320 cells/group:p<0.05). Pharmacologically inducing mitochondrial fusion using mdivi-1, a small molecule Drp1 inhibitor, reproduced the beneficial effects. Crucially, elongated interfibrillar mitochondria were identified in the adult rodent heart using confocal and electron microscopy. Finally, inducing mitochondrial fusion with mdivi-1 in adult murine cardiomyocytes reduced cell death following simulated ischaemia-reperfusion injury (34.0±1.9% vs 46.0±1.1%:N>250 cells/group:p<0.05), and reduced infarct size in the in vivo murine heart (21.0±2.2% vs 48.0±4.5% in control;N=6 animals/group:p<0.05). Conclusions: Inducing mitochondrial fusion protects the heart against ischaemia-reperfusion injury. These findings provide a novel pharmacological target for cardioprotection.